1986
DOI: 10.1063/1.555769
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Key Organic Oxygen Compounds in the Carbon Range C1 to C4. Part 2. Ideal Gas Properties

Abstract: The ideal gas thermodynamic properties of forty-four key organic oxygen compounds in the carbon range C 1 to C 4 have been calculated by a statistical mechanical technique. The properties determined are the heat capacity (C;), entropy {S' (T)-S' (O)}, enthalpy {Jr (T)-Jr (O)}, and Gibbs energy function {Go (T)-Jr (O)} IT. The calculations have been performed, in most cases, over the temperature range 0 to 1500 K and at 1 bar. The contributions to the thermodynamic properties of compounds having internal-or pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 20 publications
12
68
1
Order By: Relevance
“…The effect was small enough to ignore in the case of methyl carbamate since the molecule is heavier, while additional higher order terms were necessary for methyl formate. Willaert et al (2006) suggested the cause of the deviations to be perturbations from the first excited vibrational states of the low-frequency modes of COC bending (318 cm À1 ) and CÀO torsion (332 cm À1 ; Chao et al 1986). These states are rather high in energy, however, while the first excited CH 3 torsional state (v t ¼ 1) lies only 130 cm À1 above the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was small enough to ignore in the case of methyl carbamate since the molecule is heavier, while additional higher order terms were necessary for methyl formate. Willaert et al (2006) suggested the cause of the deviations to be perturbations from the first excited vibrational states of the low-frequency modes of COC bending (318 cm À1 ) and CÀO torsion (332 cm À1 ; Chao et al 1986). These states are rather high in energy, however, while the first excited CH 3 torsional state (v t ¼ 1) lies only 130 cm À1 above the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no experimental data allowing to an estimate ΔC cl x (T ) and hence H cl x (T ) in the 100−200 K range temperature for the guest molecules CO, CO 2 and H 2 S used in this paper. However, the heat capacities of clathrate hydrates have been measured over a wide temperature range, moslty from 85 K to 270 K, for clathrate hydrates of structure I as Xe, CH 4 , C 2 H 6 (Handa 1986a,b), and for structure II as tetrahydrofuran (Leaist et al 1982;Handa et al 1984;Yamamuro et al 1988a), ethylene oxide (Leaist et al 1982;Yamauro et al 1990), propylene oxide, 1.3-dioxolane, 2.5-dihydrofuran, 1.3-dioxane (Handa 1985), acetone (Kuratomi et al 1991), Ar (Yamamuro et al 1988b), Kr, C 3 H 8 and iC 4 H 10 (Handa 1986a,b (Chao et al 1973), tetrahydrofuran (Chao et al 1986) and assuming the values of 5 2 R for the noble gases Xe and Kr, we obtain a ratio…”
Section: Enthalpy Of Formation and Dissociation Of Clathratesmentioning
confidence: 99%
“…The activation energy we have estimated by direct kinetic experiments is E 1 ≈ 2.3 kJ mol -1 , which basically confirms the assumption of King et al [5]. Therefore, we have re-evaluated the standard enthalpy of formation of acetonyl by taking the experimental data of these authors and making use of our E 1 and auxiliary thermochemical data from recent sources [10], [24], [25], [26]. The recalculation has returned -23 kJ mol -1 for ∆ f H°2 98 (CH 3 COCH 2 ), that is, the very same value as reported by King et al [5].…”
Section: Thermochemical Implicationsmentioning
confidence: 63%